2020
DOI: 10.1038/s41467-020-17451-7
|View full text |Cite
|
Sign up to set email alerts
|

PDZD8 interacts with Protrudin and Rab7 at ER-late endosome membrane contact sites associated with mitochondria

Abstract: Endosomes are compositionally dynamic organelles that regulate signaling, nutrient status and organelle quality by specifying whether material entering the cells will be shuttled back to the cell surface or degraded by the lysosome. Recently, membrane contact sites (MCSs) between the endoplasmic reticulum (ER) and endosomes have emerged as important players in endosomal protein sorting, dynamics and motility. Here, we show that PDZD8, a Synaptotagmin-like Mitochondrial lipid-binding Proteins (SMP) domain-conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
103
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(119 citation statements)
references
References 55 publications
15
103
1
Order By: Relevance
“…MAMs convey calcium signaling between the IP 3 R and the mitochondrial calcium uniporter (MCU), the channel responsible for Ca 2+ uptake into the mitochondrial matrix. Other recently described proteins that maintain MAM integrity are DJ-1 (oncoprotein encoded in PARK7 gene) ( Xu et al, 2018 ; Liu Y. et al, 2019 ; Basso et al, 2020 ) and PDZ domain-containing protein 8 (a synaptotagmin-like mitochondrial lipid-binding protein domain-containing ER transmembrane protein) that has been implicated in ER-dependent mitochondrial calcium homeostasis ( Hirabayashi et al, 2017 ; Elbaz-Alon et al, 2020 ), while pannexin 2 has been reported to sensitize cancer cells to apoptotic stimuli ( Le Vasseur et al, 2019 ). In triple-negative breast cancer (TNBC), MCU silencing disturbs calcium uptake, enhancing alternative pathways such as SOCE, whereas the reduction of mitochondrial calcium levels inhibits cell migration in cancer cell lines.…”
Section: Membrane Contact Sitesmentioning
confidence: 99%
“…MAMs convey calcium signaling between the IP 3 R and the mitochondrial calcium uniporter (MCU), the channel responsible for Ca 2+ uptake into the mitochondrial matrix. Other recently described proteins that maintain MAM integrity are DJ-1 (oncoprotein encoded in PARK7 gene) ( Xu et al, 2018 ; Liu Y. et al, 2019 ; Basso et al, 2020 ) and PDZ domain-containing protein 8 (a synaptotagmin-like mitochondrial lipid-binding protein domain-containing ER transmembrane protein) that has been implicated in ER-dependent mitochondrial calcium homeostasis ( Hirabayashi et al, 2017 ; Elbaz-Alon et al, 2020 ), while pannexin 2 has been reported to sensitize cancer cells to apoptotic stimuli ( Le Vasseur et al, 2019 ). In triple-negative breast cancer (TNBC), MCU silencing disturbs calcium uptake, enhancing alternative pathways such as SOCE, whereas the reduction of mitochondrial calcium levels inhibits cell migration in cancer cell lines.…”
Section: Membrane Contact Sitesmentioning
confidence: 99%
“…This analysis uncovered PDZD8, in addition to VAP-A and VAP-B, as a key binding partner of protrudin ( Elbaz-Alon et al, 2020 ; Shirane et al, 2020b ). An independent study also identified protrudin as a binding partner of PDZD8 ( Elbaz-Alon et al, 2020 ). PDZD8 is a mammalian paralog of yeast Mmm1, a subunit of the ER-mitochondrial encounter structure (ERMES) complex.…”
Section: The Protrudin-pdzd8 Complex At Er-endosome Mcssmentioning
confidence: 91%
“…A differential proteomics analysis of brain extracts from wildtype and protrudin-deficient mice was performed to identify proteins that might function cooperatively with protrudin at ER-endosome MCSs. This analysis uncovered PDZD8, in addition to VAP-A and VAP-B, as a key binding partner of protrudin (Elbaz-Alon et al, 2020;Shirane et al, 2020b). An independent study also identified protrudin as a binding partner of PDZD8 (Elbaz-Alon et al, 2020).…”
Section: The Protrudin-pdzd8 Complex At Er-endosome Mcssmentioning
confidence: 95%
See 1 more Smart Citation
“…Recent studies implicated PDZD8, an ER-associated protein, and Protrudin together with the late endosomal protein Rab7 as main components of ER-endosome contact sites [292]. PDZD8 is also a component of the ER-mitochondria MCSs [293] and enables the recruitment of mitochondria to ER-endosomal MCS in order to regulate lipid transport and endosomal function [292]. Studying the significance of such complex inter-organellar interactions facilitated by multiple proteins in the context of axon growth and regeneration will be an interesting future area of research.…”
Section: Er-lysosomes/late Endosomes Interactionsmentioning
confidence: 99%